2012
DOI: 10.1016/j.bmc.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Covalent protein–oligonucleotide conjugates by copper-free click reaction

Abstract: Covalent protein-oligodeoxynucleotide (protein-ODN) conjugates are useful in a number of biological applications, but synthesizing discrete conjugates—where the connection between the two components is at a defined location in both the protein and the ODN—under mild conditions with significant yield can be a challenge. In this article, we demonstrate a strategy for synthesizing discrete protein-ODN conjugates using strain-promoted azide-alkyne [3+2] cycloaddition (SPAAC, a copper-free “click” reaction). Azide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…More efficient results were obtained using bioorthogonal approaches in which the reactive groups do not modify the activity of the biomolecules. Specifically, bioorthogonal methods such as copper‐catalyzed azide‐alkyne [3+2] cycloaddition or oxime and hydrazone ligation have been proposed . In addition, several bifunctional cross‐linkers have been also described to produce protein conjugates ,.…”
Section: Methodsmentioning
confidence: 99%
“…More efficient results were obtained using bioorthogonal approaches in which the reactive groups do not modify the activity of the biomolecules. Specifically, bioorthogonal methods such as copper‐catalyzed azide‐alkyne [3+2] cycloaddition or oxime and hydrazone ligation have been proposed . In addition, several bifunctional cross‐linkers have been also described to produce protein conjugates ,.…”
Section: Methodsmentioning
confidence: 99%
“…Aiming to address this limitation, Dozier et al analysed how different FTase mutations within the active site could be used to better accommodate these larger analogues. 259 Based on the crystal structures of FTase and previously reported literature, 260 three key residues were identified that were in close contact with the third isoprenoid unit of FPP. Accordingly, three mutants were prepared, including W102A, Y154A, and Y205A.…”
Section: Enzymatic Protein Labelling Strategiesmentioning
confidence: 99%
“…To reduce the toxic damage of copper ions, Khatwani et al used a copperfree click reaction (e.g. strain-promoted [3 + 2] azide-alkyne cycloaddition) to produce protein-DNA conjugates [51]. Francis and coworkers reported a protein bioconjugation at an N-terminal amino acid via a pyridoxal 5′-phosphate (PLP)mediated transamination reaction [52], and Takeda et al reported the development of a method to chemically modify an oligonucleotide to a N-terminal cysteine of a protein [53].…”
Section: Protein-dna Bioconjugationmentioning
confidence: 99%